MANAJAMEN LABA PADA PERISTIWA PERGANTIAN CHIEF EXECUTIVE OFFICER DI PERUSAHAAN PUBLIK SEKTOR JASA KEUANGAN DI INDONESIA - Wijaya, Bayu Artha; Ardiana, Putu Agus (E-Jurnal Akuntansi, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 This study was conducted to examine the practice of profit management at moment of chief executive officer change at the finance service sector public company in Indonesia, it was used purposive sampling so that obtained 50 companies. Analysis technique have been used was multiple regression analysis and hypotesis test by using independent sample t –test. Based on the value of discretioner acrual IDA) Mofied Jones Model with s i gnificancy level of 5%. The result showed that at moment of CEO change occur the practice of earnings management that income increaseing in the end of old CEO occupation and income decreasing at begining occupation of new CEO. Change of CEO continue and non-continue have not difference on earnings management at moment of chief executive officer change at the financial service sector public company in Indonesia.
Keywords: earnings management, chief executive officer